Changes in the growth and physiological property of tea tree after aviation mutagenesis and screening and functional verification of its characteristic hormones - Jia, Miao; Chen, Yiling; Zhang, Qi; Wang, Yuhua; Li, Mingzhe; Pang, Xiaomin; Hong, Lei; Lin, Shaoxiong; Jia, Xiaoli; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2024)
Aerospace breeding is a breeding technique that utilizes a spacecraft to position plants in a space environment for mutagenesis, which is conducive to rapid mutagenesis for the screening of superior plant varieties. In this study, tea trees with aviation mutagenesis (TM) and those without aviation mutagenesis (CK) were selected as research subjects to analyze the effects of aviation mutagenesis on the growth, physiological properties, and hormone metabolism of tea trees, and to further screen the characteristic hormones and validate their functions. The results showed that the leaf length, leaf width, and leaf area of TM tea trees were significantly larger than those of CK. The growth indexes, the photosynthetic physiological indexes (i.e., chlorophyll content, intercellular CO2 concentration, stomatal conductance, transpiration rate, and photosynthetic rate), and the resistance physiological indexes (i.e., superoxide dismutase, peroxidase, catalase, and soluble sugar) were significantly higher in TM than in CK. Hormone metabolome analysis showed that four characteristic hormones distinguished CK from TM, namely, l-tryptophan, indole, salicylic acid, and salicylic acid 2-O-β-glucoside, all of which were significantly more abundant in TM than in CK. These four characteristic hormones were significantly and positively correlated with the growth indexes, tea yield, and the photosynthetic and resistance physiological indexes of tea trees. The leaf area, chlorophyll content, photosynthetic rate, and superoxide dismutase activity of tea tree seedlings after spraying with the four characteristic hormones were significantly increased, in which salicylic acid and salicylic acid 2-O-β-glucoside were more favorable to increase the leaf area and superoxide dismutase activity, while l-tryptophan and indole were more favorable to increase the leaf chlorophyll content and photosynthetic rate. It can be observed that aviation mutagenesis improves the accumulation of the characteristic hormones of tea trees, enhances their photosynthetic capacity, improves their resistance, promotes their growth, and then improves the tea yield.